Ambivalent stereotypes of nurses and physicians: impact on students’ attitude toward interprofessional education - Sollami, Alfonso; Caricati, Luca; Mancini, Tiziana (Acta Biomedica Atenei Parmensis, 2015)
Background and aim of the work. Nurse-physician stereotypes have been proposed as a factor hindering interprofessional collaboration among practitioners and interprofessional learning among nursing and medical students. Using socio-psychological theories about ambivalent stereotypes, the present work aimed to analyse: a) the content of nurse and physician stereotypes held by nursing and medical students and b) the role of auto-stereotype on students’ attitude toward interprofessional education (IPE). Methods. A cross-sectional on-line survey was adopted and a questionnaire was emailed to 205 nursing students and 151 medical students attending an Italian university. Results. Nursing and medical students shared the stereotypical belief that nurses are warmer but less competent than physicians. Nurses and physicians were basically depicted with ambivalent stereotypes: nurses were seen as communal, socially competent and caring but less competent, not agentic and less autonomous, while physicians were seen as agentic, competent and autonomous, but less communal, less collectivist and less socially competent. Moreover, a professional stereotypical image impacted the students’ attitude toward IPE. More precisely, when nurses and physicians were seen with classic ambivalent stereotypes, both nursing and medical students were less favourable towards interprofessional education programmes. Conclusions. The content of professional stereotypes of healthcare students was still linked to classical views of nurses as caring and physicians as curing. This seemed to limit students’ attitude and intention to be engaged in IPE.